Extracellular ATP Mediates Cancer Cell Migration and Invasion Through Increased Expression of Cyclooxygenase 2 - Sharma, Shilpa; Kalra, Harshit; Akundi, Ravi Shankar (Frontiers in Pharmacology, 2021)
The tumour microenvironment plays a major role in the ability of the tumour cells to undergo metastasis. A major player of tumours gaining metastatic property is the inflammatory protein, cyclooxygenase 2 (COX-2). Several tumours show upregulation of this protein, which has been implicated in mediating metastasis in various cancer types such as of colon, breast and lung. In this report, we show that the concentration of extracellular ATP (eATP) is increased in response to cell death mediated by chemotherapeutic agents such as doxorubicin. By using three different cell-lines – HeLa (cervical), IMR-32 (neuronal) and MCF-7 (breast) – we show that this eATP goes on to act on purinergic (P2) receptors. Among the various P2 receptors expressed in these cells we identified P2X7, in IMR-32 and MCF-7 cells, and P2Y12, in HeLa cells, as important in modulating cell migration and invasion. Downstream of the P2 receptor activation, both p42/44 mitogen-activated protein kinase (MAPK) and the p38 MAPK are activated in these cells. These result in an increase in the expression of COX-2 mRNA and protein. We also observe an increase in the activity of matrix metalloproteinase 2 (MMP-2) enzyme in these cells. Blocking the P2 receptors not only blocks migration and invasion, but also COX-2 synthesis and MMP-2 activity. Our results show the link between purinergic receptors and COX-2 expression. Increased levels of ATP in the tumour microenvironment, therefore, leads to increased COX-2 expression, which, in turn, affords migratory and invasive properties to the tumour. This provides P2 receptor-based anti-inflammatory drugs (PBAIDs) a potential opportunity to be explored as cancer therapeutics.